The post-diagnosis sleep quality of patients with Parkinson's disease. (2nd August 2021) - Fujii, Chieko
Abstract : Background: Addressing the complex factors associated with Parkinson's disease (PD) requires patient interventions to be implemented by nurses and caregivers that consider personality traits and their relationship to sleep quality. Aims: To assess the sleep quality and personality traits of patients with PD pre- and post-diagnosis and determine how these factors affect patients' quality of life. Methods: The authors mailed a self-reporting questionnaire survey to all 822 members of the Japanese PD Association of Tokyo in January 2017. The overall response rate was 48.4%, and the effective response rate was 34.3%. A total of 282 participants (136 men and 146 women) were enrolled. Each patient responded to questions regarding their sex, age and primary symptoms. Participants also provided responses to questions about the hours slept per night and hours spent napping, as well as the number of toilet visits during sleep and outcomes of Type A behavioural tests. Findings: Patients with PD reported a post-diagnosis decrease in sleep time and an increase in napping time. The study subjects also reported becoming tense easily, but they did not report feeling irritated or angry. The subjective assessment indicated a post-diagnosis worsening of sleep quality in patients with PD. Conclusions: Although the underlying mechanisms of PD are not yet fully understood, patients with PD require comprehensive strategies for care that should include actions such as encouragement of patients with PD to participate in society and to perform appropriate activities that enhance sleep quality.